Freedom for Catalonia? Catalan nationalism, Spanish identity, and the Barcelona Olympic Games - Hargreaves, John (Cambridge University Press, 2000)
Although the fight for independence by national minorities has received much attention recently, there is no study of how globalised sport in its most advanced form can help to stimulate it. This book shows how the 1992 Olympic Games raised the tension that already existed between Catalonia and Spain, from the time they were awarded to Barcelona until they opened. John Hargreaves analyses and explains the way in which the conflict developed and eventually was resolved, in terms of the special characteristics of Catalan nationalism, the nature of the new Spanish democracy and the special role played by the International Olympic Committee. This book will be relevant to academics, researchers and postgraduates specialising in nationalism and Catalan nationalism, as well as being of interest to teachers, researchers and students of political sociology, cultural studies and sports studies, and professionals working in the fields of culture, sport, recreation and leisure